Response to Pazopanib in Patients With Relapsed Osteosarcoma. Issue 4 (May 2020) - Elete, Kunal R.; Albritton, Karen H.; Akers, Lauren J.; Basha, Riyaz; Ray, Anish
Abstract : Axial skeleton primary tumor, metastatic disease at presentation, incomplete surgical resection, and <90% tumor necrosis have all been known to influence prognosis adversely in osteosarcoma. Relapse of osteosarcoma, typically occurring within the first 18 months of therapy, with an incidence rate of 50% is treated with surgery, chemotherapy, and targeted therapy. Here, we discuss 2 patients treated with pazopanib, a multi–tyrosine kinase inhibitor presently approved to treat renal cell carcinoma and soft tissue sarcomas. Case 1 achieved positive response and remains on pazopanib. Case 2 sustained gastrointestinal toxicity requiring suspension of drug, despite achieving stable disease.